Strategi Penanggulangan Library Anxiety Pada Pengguna Perpustakaan - Tri Anggun Setyo Putri; Mariani Noor, Nina (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The library functions as a center for information, education, research, cultural conservation, and a place of recreation that is very important for the community. However, in reality, many users experience the phenomenon of library anxiety which affects the low effectiveness of library services. This study aims to identify the symptoms of library anxiety and to explore the role and competence of librarians in overcoming it. In the literature study method, this article collects various literatures to analyze the causal factors, descriptions, and solutions to the phenomenom. It was found that library anxiety is due to psychological factors such as fear of asking questions, lack of self-confidence, and concerns about the use of library facilities that are considered complicated. Symptoms that occur include psychological changes, avoidance behavior, and cognitive disorders. To reduce this library anxiety, librarians must apply an empathy-based service approach that strengthens information capability programs, provides proactive services, and creates a friendly and integrated library environment. The findings of this study highlight the importance of psychological and structural strategies in supporting users to overcome library anxiety. So that it can improve the effectiveness and quality of library services as a whole.